2021
DOI: 10.3390/jcm10184062
|View full text |Cite
|
Sign up to set email alerts
|

Selective Arterial Embolization of Renal Angiomyolipomas with a N-Butyl Cyanoacrylate-Lipiodol Mixture: Efficacy, Safety, Short- and Mid-Term Outcomes

Abstract: Selective arterial embolization (SAE) for renal angiomyolipoma (rAML) is effective to treat or prevent bleeding. We report our experience using a cyanoacrylate–Lipiodol mixture. We performed a single-center retrospective review of all rAMLs embolized with cyanoacrylate glue between July 2014 and June 2020. Demographics, tuberous sclerosis complex (TSC) status, clinical presentation, angiography features, and follow-up data were recorded. Pre- and post-procedure rAML sizes and volumes were estimated from comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Our cohort did have complications with post-embolization syndrome (PES) presenting in 27% of our cohort. This is in line with similar reviews with a mean incidence ranging between 33 and 60% 5,11,12 and is an expected sequalae of embolization. Major complications were present in five patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our cohort did have complications with post-embolization syndrome (PES) presenting in 27% of our cohort. This is in line with similar reviews with a mean incidence ranging between 33 and 60% 5,11,12 and is an expected sequalae of embolization. Major complications were present in five patients.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the extent of AML shrinkage induced by TAE is affected by several AML characteristics, including tumor composition and initial tumor size. AMLs with a lower fat content are reported to undergo greater decreases in tumor volume after TAE (1,9,15,16), as are smaller AMLs (1,8). Differences in these parameters between AMLs included in this pilot study may underlie the differences in initial LDH elevation and subsequent tumor volume reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of nephrectomy, superselective arterial embolization (SAE) is a minimally invasive technique that can treat dysplastic vessels and reduce tumor size ( 9 , 10 ). By superselecting the arteries, SAE can preserve renal function and decrease severe complications ( 8 , 11 ). Because of the effectiveness and safety, SAE is also gradually used as a prophylactic treatment option to avoid RAML rupture or enlargement ( 12 ).…”
Section: Introductionmentioning
confidence: 99%